Handbook of local anesthesia - Malamed, Stanley F., 1944- (St. Louis : Mosby, 2004)
Includes photographs and line drawings to provide clear instruction, plus tables and boxes for quick reference to drugs, techniques and dosages, this is a practical how-to manual of local anaesthesia.
pt. 1. The drugs -- 1. Neurophysiology -- 2. Pharmacology of local anesthetics -- 3. Pharmacology of vasoconstrictors -- 4. Clinical action of specific agents -- pt. 2. The armamentarium -- 5. The syringe -- 6. The needle -- 7. The cartridge -- 8. Additional armamentarium -- 9. Preparation of the armamentarium -- pt. 3. Techniques of regional anesthesia in dentistry -- 10. Physical and psychological evaluation -- 11. Basic injection technique -- 12. Anatomical considerations -- 13. Techniques of maxillary anesthesia -- 14. Techniques of mandibular anesthesia -- 15. Supplemental injection techniques -- 16. Local anesthetic considerations in dental specialties -- pt. 4. Complications, legal considerations, questions and future -- 17. Local complications -- 18. Systemic complications -- 19. Legal considerations / 20. Future trends in pain control -- 21. Questions -- Appendix A : Overview of CDC hand hygiene guidelines.
Selected illustrations by Imagineering Scientific and Technical Artworks, Inc.
Includes bibliographical references and index.
Keywords: Anesthesia, Dental; Anesthesia, Local; Anesthetics, Local -- pharmacology; Injections; Anesthesia in dentistry; Local anesthesia; Dental anesthesia